Pemberdayaan Masyarakat melalui Pengelolaan Sampah dalam Meningkatkan Kesejahteraan Masyarakat - Anggraeni Seltiawati; Asep Shodiqin; Fathin Anjani Hilman (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2022)
This report aims to know process of waste management in Bank Sampah Induk in Cimahi to programming and producing of impowerment by effort improved community prosperity. This is a qualitative research and description method. Results of research evinced that impowerment from Bank Sampah Induk Cimahi can improved community prosperity. Impowerment process is meant socialisation, education, management waste training, monitor, and evaluation. Impowerment waste can reduce rubbish that throw away to garbage landfill and improve community awareness about waste management. This is achieved by good connection of community role and government to problem solving waste in Cimahi.